Case report of multiple pustules of the bilateral lower limbs caused by a granulocyte colony‐stimulating factor‐producing solid pseudopapillary tumour of the pancreas. (20th August 2017) - Iwata, Y.; Kobayashi, T.; Kuroda, M.; Mizoguchi, Y.; Arima, M.; Numata, S.; Watanabe, S.; Yagami, A.; Matsunaga, K.; Sugiura, K.
Abstract : What's already known about this topic? Granulocyte colony‐stimulating factor (G‐CSF) is known to induce neutrophilic dermatoses such as Sweet syndrome, pyoderma gangrenosum and Behçet's disease when used therapeutically. Although the pathogenesis of neutrophilic dermatoses remains unknown, previous studies have suggested that G‐CSF might play an important role. What does this study add? Neutrophilic skin eruptions in this case promptly diminished after the resection of a solid pseudopapillary tumour (SPT) of the pancreas. G‐CSF immunostaining was positive for SPT cells, and serum G‐CSF levels were elevated before SPT resection and normalized after the tumour resection. This is a unique case report of neutrophilic dermatoses related to a G‐CSF‐producing SPT, which was clearly shown by the clinical course, immunostaining and serum G‐CSF levels. Linked Comment:Seminara and Pomeranz. Br J Dermatol 2017; 177:905–906 . Summary: Here we report a rare case of neutrophilic dermatoses related to a granulocyte colony‐stimulating factor (G‐CSF)‐producing solid pseudopapillary tumour (SPT). The patient was a 39‐year‐old woman presenting with scattered pustules and crusts of the palms, heels and thighs and plaques of the bilateral lower legs. The skin biopsy revealed dense neutrophil infiltration in the epidermis to the dermis. A pancreatic head tumour was detected using computed tomography. A pathological examination of the resected specimen suggested an SPT. As the skin eruption promptly disappeared after SPT resection, we hypothesized that SPT secretes growth factors including epidermal growth factor (EGF) and G‐CSF. The SPT cells stained positive for both EGF and G‐CSF tumour cells. The serum levels of interleukin (IL)‐6 and IL‐10 and tumour necrosis factor‐α were within normal limits before and after the SPT resection. In contrast, the serum IL‐8, EGF and G‐CSF levels decreased after the SPT resection. This is a rare case of neutrophilic dermatoses related to a G‐CSF‐producing SPT. The present case suggests that physicians should be aware that a G‐CSF‐producing tumour is a differential diagnosis to consider in patients with unusual aseptic pustulosis.